BRAFV600E remodels the melanocyte transcriptome and induces BANCR to regulate melanoma cell migration - Flockhart, Ross J.; Webster, Dan E.; Qu, Kun; Mascarenhas, Nicholas; Kovalski, Joanna; Kretz, Markus; Khavari, Paul A. (Genome Research, 2012)
Aberrations of protein-coding genes are a focus of cancer genomics; however, the impact of oncogenes on expression of the ∼50% of transcripts without protein-coding potential, including long noncoding RNAs (lncRNAs), has been largely uncharacterized. Activating mutations in the BRAF oncogene are present in >70% of melanomas, 90% of which produce active mutant BRAFV600E protein. To define the impacts of oncogenic BRAF on the melanocyte transcriptome, massively parallel cDNA sequencing (RNA-seq) was performed on genetically matched normal human melanocytes with and without BRAFV600E expression. To enhance potential disease relevance by verifying expression of altered genes in BRAF-driven cancer tissue, parallel RNA-seq was also undertaken of two BRAFV600E-mutant human melanomas. BRAFV600E regulated expression of 1027 protein-coding transcripts and 39 annotated lncRNAs, as well as 70 unannotated, potentially novel, intergenic transcripts. These transcripts display both tissue-specific and multi-tissue expression profiles and harbor distinctive regulatory chromatin marks and transcription factor binding sites indicative of active transcription. Coding potential analysis of the 70 unannotated transcripts suggested that most may represent newly identified lncRNAs. BRAF-regulated lncRNA 1 (BANCR) was identified as a recurrently overexpressed, previously unannotated 693-bp transcript on chromosome 9 with a potential functional role in melanoma cell migration. BANCR knockdown reduced melanoma cell migration, and this could be rescued by the chemokine CXCL11. Combining RNA-seq of oncogene-expressing normal cells with RNA-seq of their corresponding human cancers may represent a useful approach to discover new oncogene-regulated RNA transcripts of potential clinical relevance in cancer.
10.1101/gr.140061.112